Oil and gas industrial agglomeration in the Campos Basin productive region: knowledge systems, technological changes and innovation (Revista de Administração, 2008)
The main objective of this paper is to investigate the oil and gas industrial agglomeration in the Campos Basin production region verifying the possibility of this geographical cluster of firms, independent of its nomenclatures (cluster, milieu, network, industrial district, arrangement, local systems, and others), to consist in a feature that contributes to the innovative activities of the firms localized there. The fundaments of this research are based on two different paths: a theoretical and an empirical one. The theoretical path consists of a hybrid analytical model combining elements from the cluster and innovation systems approach. The empirical path is based on ten case studies with firms localized in the agglomeration, supplying goods and services which are technologically complex, and acting in areas with intense technological dynamism. The main contributions of this work are centred on the industrial agglomeration characterization, under the technological complexity and dynamism features, and on the results of the empirical study showing evidences for the existence of some groups of firms where the industrial agglomeration plays a fundamental role for their innovative activities.